PENDAMPINGAN SISTEM MANAJEMEN PEMASARAN BUAH JAMBU KRISTAL DI DESA LABRUK KABUPATEN LUMAJANG - Roshiful Aqli Qosyim; Hafid Hafid; Hairul Ulum (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2024)
The article describes assistance with the crystal guava fruit marketing management system in Labruk Village, Lumajang Regency. This service activity is carried out using the participatory rural approach (PRA) method, which educates the community through counseling, demonstrations, and mentoring. Mentoring participants are employees of PT. Fresh Kristal and the group of crystal guava farmers in Labruk Village, Lumajang Regency, number 35 people, and the community. PT. The results of the assistance show that PT. Fresh Kristal in carrying out marketing activities, which can be analyzed through the 4P marketing mix: product, price, promotion, and distribution. Each marketing mix has operational sub-mix criteria